Respiratory Distress Observation Scale Italian Version: Cultural-Linguistic Validation and Psychometric Properties. Issue 2 (8th April 2021) - Tinti, Stefania; Destrebecq, Anne; Terzoni, Stefano; De Maria, Beatrice; Falcone, Graziella; Da Col, Daria; Pairona, Giulia; Longhi, Carla; Giudici, Elisa; Pidone, Irene Maria; Alberti, Annalisa; Sofia, Michele; et al.
Abstract : Dyspnea can be assessed using self-rating scales but, as death approaches, self-reporting becomes difficult. The validated Respiratory Distress Observation Scale measures dyspnea distress. The aim of this study was to develop the Italian version of the Respiratory Distress Observation Scale and to examine its psychometric properties. This was a cross-sectional study, analyzing cultural and linguistic validation, content validity, and psychometric properties. Eighty-nine palliative care subjects were enrolled to validate the Italian version of the Respiratory Distress Observation Scale. Patients had an average age of 74.5 (SD, 11.6) years, and 52% (n = 46) were female. Fourteen experts in palliative care evaluated the Italian Respiratory Distress Observation Scale in terms of the content validity ratio and the content validity index (CVI). The Italian Respiratory Distress Observation Scale was reported with an internal consistency (Cronbach α value) of .72 and an overall substantial interrater reliability (Cohen κ method). The Italian Respiratory Distress Observation Scale achieved a scale-level CVI of 93%, an items-level CVI of greater than 86%, and a minimum content validity ratio value of 0.71. A weak positive correlation was found between the Respiratory Distress Observation Scale and the Dyspnea Visual Analog Scale scores (0.374; P < .001). The Italian Respiratory Distress Observation Scale showed good reliability and validity for patients in palliative care. The Respiratory Distress Observation Scale measured respiratory distress in patients nearest to death.